Self-injury from early adolescence to early adulthood: age-related course, recurrence, and services use in males and females from the community. - Steinhoff, Annekatrin; Ribeaud, Denis; Kupferschmid, Stephan; Raible-Destan, Nesrin; Quednow, Boris B.; Hepp, Urs; Eisner, Manuel; Shanahan, Lilly (European Child & Adolescent Psychiatry, 2021)
Adolescent self-injury is a widespread public health problem, but long-term longitudinal studies from European countries are rare. Self-injury in males and sex differences are poorly understood. This study describes the prevalence, frequency, age-related course, and recurrence of, and mental health services use related to adolescent self-injury. Data came from a Swiss prospective-longitudinal cohort study (N = 1482). Adolescents (52% male) reported frequency of self-injury and mental health services use (including reasons for and types of services use, hospitalizations) at ages 13, 15, 17, and 20. Between ages 13–20, 27% of adolescents reported self-injury at least once. In males, prevalence decreased from 12 to 5%; in females self-injury peaked at age 15 (16%) and then decreased (11% at age 20). In males, recurrence of self-injury increased after age 15 (from odds ratio [OR] < 3 to OR > 10); in females, recurrence was high from age 13 onwards (OR > 5). Predictors of recurrence included childhood/early adolescent internalizing symptoms and early self-injury onset. Typically, less than half of adolescents with self-injury used mental health services. Males with self-injury used services mainly for externalizing problems, learning difficulties, and attention/concentration problems; females for depression or self-injury, family problems, and victimization. Types of services used changed with age, and adolescents with self-injury had increased rates of hospitalization. There are notable sex differences in the longitudinal course of self-injury and reasons for related mental health services use. Treating early internalizing symptoms could be a promising target for preventing recurrent self-injury. Males are at particular risk of not receiving adequate treatment for self-injury.